CHANGES OF TOTAL FLAVONOIDS AND PHENOLICS CONTENTS OF INDONESIAN FERMENTED SOY-BASED PRODUCTS DURING PROCESSING AND AN OVERVIEW OF THEIR BENEFITS TO HUMAN HEALTH - , MARGARET IRMA ARIANI; , Prof. Dr. Ir. Y. Marsono, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Soybeans are rich in antioxidants especially flavonoid and phenolics. They are believed to be effective in fighting degenerative diseases such as coronary heart disease, stroke and cancers. In most asian countries, including Indonesia, most soy-based products undergo fermentation before undergoing further processing such as boiling and frying. It is widely believed that thermal processing degrades many antioxidant components in food while fermentation enhances them. Objectives: This study tries to analyse the effects of fermentation and heat treatments on total flavonoid and phenolic contents of soy-based products as well as exploring their public-health effects. Methodology : Total flavonoids analysis is done by colorimetric assay. Total phenolic analysis is done by Folin-Ciocalteu method. A simple statistical analysis using mean and standard deviations are used for all datas produced. Results: The process of fermentation has increased the total flavonoid and phenolic contents. Hence, the TFC (total flavonoid contents) and TPC (total phenolics contens) in tempe and soy-paste are higher compared to those found in raw soybeans. Heat treatment, on the other hand, has decreased the total flavonoid and phenolic contents. The TFC and TPC of fried and boiled tempe are lower than the raw tempe.